Mesenchymal stem cell-derived exosomes enriched with miR-218 reduce the epithelial–mesenchymal transition and angiogenesis in triple-negative breast cancer cells - Samaneh Shojaei; Maryam Moradi-Chaleshtori; Mahdi Paryan; Ameneh Koochaki; Kazem Sharifi; Samira Mohammadi-Yeganeh (European Journal of Medical Research, 2023)
Abstract Background The epithelial–mesenchymal transition (EMT) and angiogenesis are morphogenetic processes implicated in tumor invasion and metastasis. It is found that the aberrant expression of microRNAs (miRNAs) contributes to these processes. Exosomes are considered potential natural vehicles for miRNA delivery in cancer therapy. miR-218 is one of the tumor suppressor miRNAs and its downregulation is associated with EMT and angiogenesis. We aimed to use adipose mesenchymal stem cells-derived exosomes (ADMSC-exosomes) for miR-218 delivery to breast cancer cells and evaluate miR-218 tumor-suppressing properties in vitro. Methods Exosomes were isolated from conditioned media of ADMSCs. miR-218 was loaded to exosomes using electroporation. mRNA expression of target genes (Runx2 and Rictor) in MDA-MB-231 breast cancer cells was evaluated by qPCR. To explore the effects of miR-218 containing exosomes on breast cancer cells, viability, apoptosis, and Boyden chamber assays were performed. The angiogenic capacity of MDA-MB-231 cells after treatment with miR-218 containing exosomes was assessed by in vitro tube formation assay. Results miR-218 mimic was efficiently loaded to ADMSC-exosomes and delivered to MDA-MB-231 cells. Exposure to miR-218 containing exosomes significantly decreased miR-218 target genes (Runx2 and Rictor) in MDA-MB-231 cells. They increased the expression of epithelial marker (CDH1) and reduced mesenchymal marker (CDH2). miR-218 restoration using miR-218 containing exosomes reduced viability, motility, invasion, and angiogenic capacity of breast cancer cells. Conclusions These findings suggest that ADMSC-exosomes can efficiently restore miR-218 levels in breast cancer cells and miR-218 can prevent breast cancer progression with simultaneous targeting of angiogenesis and EMT.